2019
DOI: 10.1021/acs.jafc.8b07087
|View full text |Cite
|
Sign up to set email alerts
|

Novel α-1,3/α-1,4-Glucosidase from Aspergillus niger Exhibits Unique Transglucosylation to Generate High Levels of Nigerose and Kojibiose

Abstract: α-Glucosidase from Aspergillus niger (AgdA; typical α-1,4-glucosidase) is known to industrially produce α-(1→ 6)-glucooligosaccharides. This fungus also has another α-glucosidase-like protein, AgdB. To learn its function, wild-type AgdB was expressed in Pichia pastoris. However, the enzyme displayed two electrophoretic forms due to heterogeneity of Nglycosylation at Asn354. The deglycosylation mutant N354D shared the same properties with wild-type AgdB. N354D demonstrated hydrolytic specificity toward α-(1→3)a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Although rAgdB expressed in P. pastoris was previously collected from culture supernatants, 7) within our study enzyme activity was not detected in the supernatant but rather in cell extracts.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Although rAgdB expressed in P. pastoris was previously collected from culture supernatants, 7) within our study enzyme activity was not detected in the supernatant but rather in cell extracts.…”
Section: Resultsmentioning
confidence: 71%
“…We found that α-1,2-, α-1,3-, and small amount of α-1,1-β-linked oligosaccharides are present throughout the transglucosylation products of AgdB from maltose and maltopentaose. Similarly, Ma et al 7) detected four oligosaccharides consisting of α-1,2-and α-1,3-glucosidic linkages, namely, kojibiose, nigerose, 3 2 -O-α-D-glucosyl-maltose, and centose in the transglucosylation products from maltose. However, these products constituted a portion of the observed transglucosylation products of rAgdB.…”
Section: Nmr Signal Assignmentmentioning
confidence: 93%
“…The reaction was initiated by adding maltose, and allowed to proceed for another 10 min. At different time intervals, samples were collected and the residual activity was assayed under the standard assay conditions [28,37] .…”
Section: Enzyme Assaymentioning
confidence: 99%
“…The supernatant was collected and stored at -20°C waiting for high performance liquid chromatography (HPLC) analysis. On the basis of the initial reaction condition, that is, the reaction last for 6 h at 37°C, pH 4.0, with the molar ratio of maltose to AA•Na set to 3:2, the influence of reaction temperature (30,37,40,45, and 50 degC), pH (100 mM sodium citrate buffer at pH 3.0-3.5 and 100 mM sodium acetate buffer at pH 4.0-5.5), and maltose/AA*Na molar ratio (1:1, 3:1 and 3:2) on the synthesis of AA-2G catalyzed by rAGL was investigated. Besides, the influence of enzyme concentrations on AA-2G synthesis was also investigated.…”
Section: Transglycosylation Catalyzed By Raglmentioning
confidence: 99%
See 1 more Smart Citation